Absence heritage: A critical analysis for awareness, preservation and resilience - Sherene A. James-Williamson; Jorjan E. Dolphy; Stephanie Y. Parker (International Journal of Geoheritage and Parks, 2024)
Traditionally, absence heritage or heritage of absence has been used for purposeful erasure of tangible and intangible elements related primarily to affective heritage and dark heritage. Current observations, however, have indicated that there is no exact definition of such heritage, persons seem to indicate absence or presence depending on the particular scenario. This limitation arises because there is heritage that is absent purely by accident, there is heritage that is purposefully erased, there is heritage that is forgotten or destroyed by natural, man-made disasters, war, or there is simply heritage that has been modified or rewritten to suit interests, all of which can affect psychology, identity and resilience. These instances of erasure include natural and man-made disasters, climate change, and museum collections held in trust for protection and preservation, to name a few. This paper recommends the extension of the current use and proposition of a definition of absence heritage to provide a more holistic view of the state of affairs. The paper presents an overview of current use, and reasons, using global examples, to aid in formulating a definition and expanding the use with strategies to reduce or mitigate erasure. With this, awareness and resilience can be built in any society.